Politik Hukum Islam di Pengadilan Agama Perbatasan: Ketegangan Antara Hukum Negara, Hukum Adat, dan Identitas Agama - Imron Hamzah (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
This study examines the dynamics of Islamic legal politics in the Religious Courts located in Indonesia’s border regions, where state law, local customary law, and Islamic law interact in complex and sometimes conflicting ways. The presence of the Religious Courts as formal state institutions represents the codified authority of Islamic family law under the national legal system. However, in border areas, these institutions often confront strong influences of local customary practices and the transnational character of religious identity that transcends political boundaries. By employing a qualitative normative approach combined with case studies of selected Religious Courts in border regions, this research explores how judges navigate the tension between upholding state law, accommodating community customs, and preserving Islamic legal values. The findings reveal that judicial practice in border areas not only reflects the legal pluralism inherent in Indonesia’s socio-legal context but also highlights the role of Religious Courts as mediators of political, cultural, and religious interests. This paper argues that the politics of Islamic law in borderland Religious Courts should be understood as a continuous process of negotiation rather than a fixed normative order. The study contributes to the discourse on Islamic legal politics by demonstrating how legal authority is constructed and contested in peripheral contexts, offering insights for the harmonization of state, religion, and local traditions in Indonesia’s legal development